THE COCONUT INDUSTRY – SOLOMON ISLANDS - Brian G.C. Smith (International Coconut Community, 1987)
The coconut plays a vital part in the culture and economy of Solomon Islands. Not only is it the main source of income to the majority of smallholders in the country it is also an important ‑ food. The Government has recently carried out a survey of the smallholder coconut sector which has produced valuable baseline data high government is basing a development programme. Whilst a replanting programme is not envisaged farmers will encouraged through demonstrations based on research findings crease the output from the existing resource to improve rural and national incomes and to ensure a continuing supply of this food for the increasing population.